2016
DOI: 10.1186/s40809-016-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cortical folding and brain arteriovenous malformations

Abstract: Background The pathogenesis of human intracranial arteriovenous malformations (AVMs) is not well understood; this study aims to quantitatively assess cortical folding in patients with these lesions. Methods Seven adult participants, 4 male and 3 female, with unruptured, surgically unresectable intracranial AVMs were prospectively enrolled in the study, with a mean age of 42.1 years and Spetzler-Martin grade range of II–IV. High-resolution brain MRI T1 and T2 sequences were obtained. After standard preprocess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The pathogenesis and biological development of brain AVMs remains poorly understood, but recent evidence suggests that aberrant angiogenesis may be embroiled in the expansion, development, and rupture of AVMs (Berman et al, 2000 ; Leblanc et al, 2009 ; Chen et al, 2014 ; Rangel-Castilla et al, 2014 ). Vasculogenesis precedes embryologic cortical folding and studies have found no difference in the cortical folding patterns in normal vs. AVM brains (Shah et al, 2016 ). Digressive expression of angiogenic factors in central nervous system is a main contributor to vascular malformations including brain AVMs (Mouchtouris et al, 2015 ).…”
Section: Avm Biology and Developmentmentioning
confidence: 99%
“…The pathogenesis and biological development of brain AVMs remains poorly understood, but recent evidence suggests that aberrant angiogenesis may be embroiled in the expansion, development, and rupture of AVMs (Berman et al, 2000 ; Leblanc et al, 2009 ; Chen et al, 2014 ; Rangel-Castilla et al, 2014 ). Vasculogenesis precedes embryologic cortical folding and studies have found no difference in the cortical folding patterns in normal vs. AVM brains (Shah et al, 2016 ). Digressive expression of angiogenic factors in central nervous system is a main contributor to vascular malformations including brain AVMs (Mouchtouris et al, 2015 ).…”
Section: Avm Biology and Developmentmentioning
confidence: 99%
“…It also prolongs the procedure and increases the utilization of contrast agents, thereby escalating the procedural risks [ 5 9 ]. These challenges lie in accessing the distal cortical arteries, which are crucial for treating various lesions and diseases in that region, including aneurysms [ 10 12 ], arteriovenous malformations [ 13 , 14 ], liver tumors [ 15 , 16 ], vascular tumors [ 17 ], and bleeding control [ 18 20 ]. Please refer to Table S1 for current limitations for these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical example, the distally cortical arteries are limited to safely and effectively access by catheters to treat various lesions and diseases around this region, such as acute ischemic stroke (AIS) 3 , 7 , 8 , aneurysm 9 , 10 , cerebral arteriovenous malformation (CAVM) 11 , 12 , dural arteriovenous fistulas (dAVFs) 13 , 14 , and brain tumors 15 , 16 . Particularly, most malignant primary brain tumors occur in the cerebral cortex, with the highest percentage of 26% developing in the frontal lobe 15 , and dAVFs and 86% of the CAVM occur in the cortical region 12 . Although occurrence rates of cortical aneurysms and AIS were reported to be 1% and lower than 15%, respectively, it has also been raised that actual rates were underestimated due to the sensitivity of medical imaging 3 , 10 .…”
Section: Introductionmentioning
confidence: 99%